Privacy or Publicity - Who Drives the Wheel? - Christina E. Bannier (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Financial markets are to a very large extent influenced by the advent of information. Such disclosures, however, do not only contain information about fundamentals underlying the markets, but they also serve as a focal point for the beliefs of market participants. This dual role of information gains further importance for explaining the development of asset valuations when taking into account that information may be perceived individually (private information), or may be commonly shared by all traders (public information). This study investigates into the recently developed theoretical structures explaining the operating mechanism of the two types of information and emphasizes the empirical testability and differentiation between the role of private and public information. Concluding from a survey of experimental studies and own econometric analyses, it is argued that most often public information dominates private information. This finding justifies central bankers' unease when disseminating news to the markets and argues against the recent trend of demanding full transparency both for financial institutions and financial markets themselves.
urn:nbn:de:hebis:30-10343
Keywords: F31; D84; D82; 330; private information; beliefs; coordination; financial crises; public information; transparency